2012
DOI: 10.1021/nn301714n
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Gold Nanoparticles: A Multiparametric Study

Abstract: The in vitro labeling of therapeutic cells with nanoparticles (NPs) is becoming more and more common, but concerns about the possible effects of the NPs on the cultured cells are also increasing. In the present work, we evaluate the effects of poly(methacrylic acid)-coated 4 nm diameter Au NPs on a variety of sensitive and therapeutically interesting cell types (C17.2 neural progenitor cells, human umbilical vein endothelial cells, and PC12 rat pheochromocytoma cells) using a multiparametric approach. Using va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
218
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 248 publications
(241 citation statements)
references
References 60 publications
14
218
3
6
Order By: Relevance
“…Figure 7A,B reveals a concentration-dependent reduction in cell-spreading, which is in line with previous reports on various types of nanoparticles [36,42,43]. Please note that for these assays, only low QDot concentrations (up to 20 nM) were selected that do not induce significant levels of acute cell death as the occurrence of apoptotic bodies or condensed cells would substantially influence the results obtained.…”
Section: Effects Of Qdot Degradation On Cell Viabilitysupporting
confidence: 90%
“…Figure 7A,B reveals a concentration-dependent reduction in cell-spreading, which is in line with previous reports on various types of nanoparticles [36,42,43]. Please note that for these assays, only low QDot concentrations (up to 20 nM) were selected that do not induce significant levels of acute cell death as the occurrence of apoptotic bodies or condensed cells would substantially influence the results obtained.…”
Section: Effects Of Qdot Degradation On Cell Viabilitysupporting
confidence: 90%
“…Consensus on the optimal design of this multiparametric method has however not yet been reached, but several examples have been proposed recently, including one from our group that is displayed in figure 2 43,127 . Methods to evaluate the different parameters are preferably biochemical or microscopy-based assays as they are easily amendable for a future screening approach 128 .…”
Section: B Multiparametric Nanotoxicity Evaluationmentioning
confidence: 99%
“…In the present work, three different cell types are used (murine C17.2 neural progenitor cells, primary human umbilical vein endothelial cells (HUVEC) and rat PC12 pheochromocytoma cells) that have previously been shown to have a high potential in cell therapy and which are excellent models for different tissue types [38,39]. Cells that were transiently expressing lysosomal associated membrane protein 1 (Lamp1) fused with a fluorescent protein (green or red) as a marker for late endosomal and lysosomal compartments were exposed to the QDots at concentrations up to 50 nM for 24 h. Cells were then analyzed by confocal microscopy, where the colocalization of the QDots and the lysosomal marker was analyzed (Fig.…”
Section: Cellular Uptake Of Gradient Alloy Qdotsmentioning
confidence: 99%
“…As NP toxicity is more closely correlated to the cellular NP level rather than the number of NPs originally administered to the cells [22], this would result in lower toxicity in PC12 cells. However, the PC12 cells, which are small cells with a limited cytoplasmic space, have been found to be very sensitive to cell stress [39]. Additionally, it has been shown that the size of the cell and its cytoplasm inversely correlates with the level of NP the cell can handle without any toxic effects [42].…”
Section: Acute and Long-term Toxicity And Oxidative Stressmentioning
confidence: 99%